Chemicalized America. - Albert, Mabel E. (Tufts Archival Research Center, 2018)
Since growing up in the Mount Washington Valley of New Hampshire, Mabel has always been fascinated by nature and the environment. She focuses her work around the ongoing conversation between humans and the earth. She utilizes the idea of a self-reflective experience, combined with the notion that humanity has, over time, begun to destroy the earth. Working primarily with oils to portray fragmented paintings, Mabel also adds sculptural elements into her works. She portrays an experience through her paintings that aims to make the audience feel emotional responsibility.; Keywords: Painting, oil paint, mirror, environment, human development, climate change, destruction, wildlife, reflection, self-reflection.